JAK Inhibitors: Prospects in Connective Tissue Diseases - You, Hanxiao; Xu, Dong; Zhao, Jiuliang; Li, Jing; Wang, Qian; Tian, Xinping; Li, Mengtao; Zeng, Xiaofeng (Clinical reviews in allergy & immunology, 2020)
The dysregulation of the JAK–STAT pathway is associated with various immune disorders. Four JAK inhibitors have been approved for rheumatoid arthritis (RA), and numerous JAK inhibitors are currently being tested in phase II and III trials for the treatment of various autoimmune inflammatory diseases. In this narrative review, we elucidate the involvement of the JAK–STAT signaling pathway in the pathogenesis of connective tissue diseases (CTDs). We also discuss the efficacy of the first- and second-generation JAK inhibitors (tofacitinib, baricitinib, ruxolitinib, peficitinib, filgotinib, upadacitinib, solcitinib, itacitinib, decernotinib, R333, and pf-06651600) for CTDs including RA, systemic lupus erythematosus, dermatomyositis, systemic sclerosis, Sjögren’s syndrome, and vasculitis, based on laboratory and clinical research findings. JAK inhibitors have great potential for the treatment of various CTDs by reducing multiple cytokine production and suppressing inflammation, with the advantages of rapid onset in an oral formulation and decreased corticosteroid dependence and the associated adverse events, especially in refractory cases. We also highlight the safety of novel JAK inhibitors, which can cause opportunistic infections, especially viral infections. Being a very recent therapeutic option, information regarding the safety of JAK inhibitors during pregnancy and for pediatric use is limited. However, it is recommended that JAK inhibitors should be avoided in pregnant and breastfeeding women. More clinical data, especially on highly selective inhibitors, are required to judge the efficacy and safety of JAK inhibition in CTDs.